2020
DOI: 10.3390/ijms21218369
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model to Investigate the Role of Helicobacter pylori in Type 2 Diabetes, Obesity, Alzheimer’s Disease and Cardiometabolic Disease

Abstract: Helicobacter pylori (Hp) is a Gram-negative bacterium colonizing the human stomach. Nuclear Magnetic Resonance (NMR) analysis of intracellular human gastric carcinoma cells (MKN-28) incubated with the Hp cell filtrate (Hpcf) displays high levels of amino acids, including the branched chain amino acids (BCAA) isoleucine, leucine, and valine. Polymerase chain reaction (PCR) Array Technology shows upregulation of mammalian Target Of Rapamycin Complex 1 (mTORC1), inflammation, and mitochondrial dysfunction. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…On the other hand, obesity is also associated with morphological and functional impairment in mitochondria that initiate insulin resistance (responsible for tau hyperphosphorylation and Aβ aggregation) peripheral inflammation, memory deficits, and oxidative stress that increase the risk of AD [ 70 , 71 , 72 ]. Cuomo et al [ 73 ] disclosed that PCR and NMR analyses showed that Helicobacter pylori could potentially modulate AD, type-2 diabetes, cardio-metabolic disease, and obesity. Helicobacter pylori induces high levels of amino acids and activates the mammalian target of rapamycin complex 1 (regulates the host’s metabolism) and branched-chain amino acids.…”
Section: Metabolic Impairment and Admentioning
confidence: 99%
“…On the other hand, obesity is also associated with morphological and functional impairment in mitochondria that initiate insulin resistance (responsible for tau hyperphosphorylation and Aβ aggregation) peripheral inflammation, memory deficits, and oxidative stress that increase the risk of AD [ 70 , 71 , 72 ]. Cuomo et al [ 73 ] disclosed that PCR and NMR analyses showed that Helicobacter pylori could potentially modulate AD, type-2 diabetes, cardio-metabolic disease, and obesity. Helicobacter pylori induces high levels of amino acids and activates the mammalian target of rapamycin complex 1 (regulates the host’s metabolism) and branched-chain amino acids.…”
Section: Metabolic Impairment and Admentioning
confidence: 99%
“…This result shows the under-appreciated opportunity offered by metabolomics to reach definitive conclusions when enrolling a small number of patients [ 58 ]. The selective power of metabolomics has been confirmed by an independent study [ 14 ].…”
Section: Resultsmentioning
confidence: 84%
“…Hp displays several more properties. Grown in the presence of low iron or high salt concentrations, the bacterium rapidly selects the carcinogenic variant FuR88H [ 13 ], which is associated with several non-gastric diseases [ 14 ]. Furthermore, Hp displays conflicting properties: it is the main risk factor for gastric carcinoma and gastric MALT lymphoma [ 7 ], but protects against esophageal adenocarcinoma, Barrett’s esophagus, and gastroesophageal reflux [ 15 ].…”
Section: Helicobacter Pylori –Human Host Interamentioning
confidence: 99%
See 2 more Smart Citations